Strategi pemasaran berkelanjutan untuk meningkatkan loyalitas konsumen di toko baju Al Baroqah - afifatus sholikhah; Vebri Fiarnanta (Universitas Nahdlatul Ulama Sidoarjo, 2026)
The This study aims to analyze the sustainable marketing strategies used by the Al Baroqah Clothing Store in Gabus Village, Grobogan, Central Java, to increase customer loyalty amidst increasingly fierce retail competition. Using a qualitative approach, data was obtained through direct observation, interviews with the owner and loyal customers, and supporting documentation. The results indicate that the Al Baroqah Clothing Store fosters customer loyalty through environmentally friendly products, consistent service, the use of WhatsApp for promotions, and after-sales service. The average customer satisfaction score is 4.05 out of 5, with key strengths being product quality and promotional interactions, although pricing still needs improvement. The study also identified obstacles such as lack of capital, consumer misunderstanding of the importance of sustainability, and potential regulatory changes. However, the store can overcome these challenges through innovation, good community relations, and flexible marketing planning. These findings emphasize the importance of sustainable marketing strategies for increasing customer trust, satisfaction, and loyalty, while supporting ethical and sustainable business growth.